Are your patients satisfied? - Acharya, Samita; Shrestha, A; Shrestha, SR; Yadav, BK; Butterworth, K (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Introduction: Patient Satisfaction is an important element in patient care. There is an association between satisfaction level, patient adherence and success of the treatment. This study was conducted to measure patient satisfaction in the department general Outpatient Department (OPD) and Emergency. Method: This was a cross sectional descriptive study conducted in Patan Hospital on 18th August 2011. All patients registering in emergency or OPD were interviewed. A questionnaire based on the Press Ganey Questionnaire was used. Satisfaction was assessed on the basis of response to each domain which included patients’ details and waiting time, registration process, physical comfort and nursing care, physician care and finally overall satisfaction with the emergency and outpatient department. Result: Total 92 patients were included from emergency. Average waiting time was 11.7 minutes with range of 2 to 35 minutes. Patients’ satisfaction was 83.6% while there was no patient whose satisfaction was below average. Patients were satisfied on behavior of staff at registration (93.5%), and unsatisfied about doctor not telling side effects of medicine (33.7%). Similarly 196 patients were included from OPD. Patient’s satisfaction was 84.7%. Satisfaction level was highest with behavior of staff at pharmacy (94%). In OPD also patients were unsatisfied with doctors not telling side effect of medicine (41.8%). Conclusion: Our study highlights importance of communication with patients, specifically about medicine side effects for satisfaction of patients in outpatient and emergency departments.